Ceracis tzotzilicus sp. nov. (Coleoptera: Tenebrionoidea: Ciidae) from Guatemala and Mexico - Souza-Gonçalves, Igor; Lopes-Andrade, Cristiano (Zootaxa, 2020)
Ceracis tzotzilicus sp. nov. is described on the basis of 200 specimens collected in San Cristóbal de las Casas (Mexico) and Yepocapa (Guatemala), at an altitude above 2000 m. Ceracis tzotzilicus resembles members of the Ceracis cucullatus species-group due to the fine and sparse pronotal punctation, but males can be distinguished by the absence of a long anterior pronotal lamina and females by the ovipositor lacking gonostyli.